2016
DOI: 10.1063/1.4958830
|View full text |Cite
|
Sign up to set email alerts
|

High coercivity in Mn-Ga-Cu alloys

Abstract: Mn-Ga-Cu alloys were produced by melt-spinning and subsequent annealing. The coercivity of the Mn-Ga-Cu alloys was dependent on the Cu content and the annealing conditions. The coercivity of the Mn65Ga20Cu15 alloy annealed at 573 K for 10 h, iHc = 23.8 kOe, was comparable to that of rare-earth-based magnets. The hard magnetic phase of the Mn65Ga20Cu15 alloy was found to be fine D022-Mn3Ga grains, formed from the fcc phase during annealing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…Thus, the annealing regime with temperature of 275 °C − 300 °C and time of 10 h − 15 h, is effective for enhancing hard magnetic parameters of the alloy ribbons. The obtained results are in good agreement with those reported by T. Saito et al for Mn 65 Ga 35-x Cu x alloy ribbons [40]. They showed that, the coercivity strongly depends on Cu concentration from 0 to 20% and annealing temperature from 200 °C to 600 °C.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, the annealing regime with temperature of 275 °C − 300 °C and time of 10 h − 15 h, is effective for enhancing hard magnetic parameters of the alloy ribbons. The obtained results are in good agreement with those reported by T. Saito et al for Mn 65 Ga 35-x Cu x alloy ribbons [40]. They showed that, the coercivity strongly depends on Cu concentration from 0 to 20% and annealing temperature from 200 °C to 600 °C.…”
Section: Resultssupporting
confidence: 92%
“…However, the obtained M s value is rather low, only 3 emu g −1 . In other studies [40,45], the substitution of Al for Ga in the Mn-Ga based alloy ribbons formed a phase with new cubic structure with space group P2 1 3 or P4 2 32 in addition to the D0 22 ferrimagnetic phase. The coercivity in the Mn 65 Ga 15 Al 20 ribbon annealed at 700 °C for 1 h is increased from 5 kOe to 9.1 kOe by contribution of the D0 22 phase.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Figure 4(b) shows the hysteresis loops of the samples annealed at 650 • C for various times. The results of our hard magnetic properties obtained on these Mn-Ga-Al samples are similar to those of other research groups on the same material [20,23,26]. From the obtained results, we selected the annealing temperature of 650 • C and time of 15 min for the hard magnetic phase.…”
Section: Resultssupporting
confidence: 80%
“…According to theoretical calculations, nanocomposite hard magnetic materials might have a maximum energy product (BH) max more than 100 MGOe [18] based on a combination of strong coercivity of hard magnetic phases and high saturation magnetization of soft magnetic phases. Recently, the Mn-Ga based hard magnetic materials have been attracting research interests as a new hard magnetic phase for the nanocomposite materials [19][20][21][22][23]. By adding elements such as Cu, Fe, Al… the D0 22 -type hard magnetic phase is formed more easily and its coercivity can exceed 10 kOe, high enough for coupling with the soft magnetic phase.…”
Section: Introductionmentioning
confidence: 99%